Socioeconomic implications of biofuels deployment through an Input-Output approach. A case study in Uruguay. (April 2019) - Lechón, Y.; de la Rúa, C.; Rodríguez, I.; Caldés, N.
Abstract: Some countries in the world aim to increase biofuel production and consumption as a way to decarbonize the transport sector and transit to a low carbon economy. Besides their potential environmental advantages compared to conventional fuels, biofuels may also bring other socioeconomic benefits. Using the Input-Output Analysis, this study has looked at the socio-economic impacts associated to the biofuels targets established in Uruguay by estimating the associated gross and net effects on production of goods and services; value added and job creation categorized into rural and non-rural. Next, the impacts on the Uruguay's balance of payments, energy security and tax revenues have been estimated and added to the previous effects. When it comes to value added, bioethanol from sugarcane ranks first among the considered biofuels with 431 million US$2018, followed by bioethanol from sorghum and biodiesel. As to job creation, around 34, 000 full time new jobs are created as a result of sugarcane bioethanol, twice as much as from biodiesel. Of these figures, rural employment share represents a 13% and 6% in the case of sugarcane bioethanol and biodiesel respectively. On concluding result from this study is that while biofuel production costs in Uruguay are higher than fossil fuel, when the economic effects on tax revenues and balance of payments are added to the previous socio-economic impacts, the total benefits from biofuels compensate the extra costs. However, this situation may be altered in the future as a result of changes in biofuel production costs, fiscal policies as well as import and export prices variations. Graphical abstract: fx1 Highlights: Biofuels production and consumption in Uruguay bring large socioeconomic benefits. Highest value added and employment (total/rural) impacts from sugarcane bioethanol. Tax collection from sorghum bioethanol is four times higher than from biodiesel. Balance of payment from biodiesel is four times higher than from sorghum bioethanol. Positive effects in energy security are higher for biodiesel than for bioethanol.